EFEKTIVITAS METODE PEMENUHAN PEMBERIAN CAIRAN INTRAVENA DENGAN INFUS POMPA PADA PASIEN ANAK DI RSI SULTAN HADLIRIN JEPARA - Sigit Nugroho; Ratna Ratna; Feri Catur Yuliani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The pump infusion method is becoming an increasingly popular choice in administering intravenous fluids. Pump infusion provides advantages in terms of dose accuracy and fluid flow rate control. Purpose: to determine the effectiveness of the intravenous fluid administration method using a pump infusion device in pediatric patients at RSI Sultan Hadlirin Jepara. Method: This study uses an experimental research type with a pre-test and post-test design. Research population The sample in this study will be taken from a population of children who receive intravenous fluid fulfillment with drip infusion of 30 people, the technique used is total sampling. Results The majority of respondents were male (63.3%), aged 1–5 years (60%), and had an average body weight of 6–10 kg (53.3%). All patients (100%) were diagnosed with illness by a doctor and required intravenous fluid therapy. After being given intravenous fluids with the pump method, most pediatric patients showed improvement in their health conditions. Conclusion: data analysis with t-Test can be seen that the Sig. (2-tailed) value = 0.003 <0.005. This means that the pump method of intravenous fluid administration is effective.